CRISPR/FnCas12a-mediated efficient multiplex and iterative genome editing in bacterial plant pathogens without donor DNA templates. - Fang Yan; Jingwen Wang; Sujie Zhang; Zhenwan Lu; Shaofang Li; Zhiyuan Ji; Congfeng Song; Gongyou Chen; Jin Xu; Jie Feng; Xueping Zhou; Huanbin Zhou (PLoS Pathogens)
CRISPR-based genome editing technology is revolutionizing prokaryotic research, but it has been rarely studied in bacterial plant pathogens. Here, we have developed a targeted genome editing method with no requirement of donor templates for convenient and efficient gene knockout in Xanthomonas oryzae pv. oryzae (Xoo), one of the most important bacterial pathogens on rice, by employing the heterologous CRISPR/Cas12a from Francisella novicida and NHEJ proteins from Mycobacterium tuberculosis. FnCas12a nuclease generated both small and large DNA deletions at the target sites as well as it enabled multiplex genome editing, gene cluster deletion, and plasmid curing in the Xoo PXO99A strain. Accordingly, a non-TAL effector-free polymutant strain PXO99AD25E, which lacks all 25 xop genes involved in Xoo pathogenesis, has been engineered through iterative genome editing. Whole-genome sequencing analysis indicated that FnCas12a did not have a noticeable off-target effect. In addition, we revealed that these strategies are also suitable for targeted genome editing in another bacterial plant pathogen Pseudomonas syringae pv. tomato (Pst). We believe that our bacterial genome editing method will greatly expand the CRISPR study on microorganisms and advance our understanding of the physiology and pathogenesis of Xoo.